The impact of localized implementation: determining the cost-effectiveness of HIV prevention and care interventions across six United States cities. (1st March 2020) - Krebs, Emanuel; Zang, Xiao; Enns, Benjamin; Min, Jeong E.; Behrends, Czarina N.; del Rio, Carlos; Dombrowski, Julia C.; Feaster, Daniel J.; Gebo, Kelly A.; Golden, Matthew; Marshall, Brandon D.L.; Metsch, Lisa R.; et al.
Abstract : Objective: Effective interventions to reduce the public health burden of HIV/AIDS can vary in their ability to deliver value at different levels of scale and in different epidemiological contexts. Our objective was to determine the cost-effectiveness of HIV treatment and prevention interventions implemented at previously documented scales of delivery in six US cities with diverse HIV microepidemics. Design: Dynamic HIV transmission model-based cost-effectiveness analysis. Methods: We identified and estimated previously documented scale of delivery and costs for 16 evidence-based interventions from the US CDC's Compendium of Evidence-Based Interventions and Best Practices for HIV Prevention. Using a model calibrated for Atlanta, Baltimore, Los Angeles, Miami, New York City and Seattle, we estimated averted HIV infections, quality-adjusted life years (QALY) gained and incremental cost-effectiveness ratios (healthcare perspective; 3% discount rate, 2018$US), for each intervention and city (10-year implementation) compared with the status quo over a 20-year time horizon. Results: Increased HIV testing was cost-saving or cost-effective across cities. Targeted preexposure prophylaxis for high-risk MSM was cost-saving in Miami and cost-effective in Atlanta ($6123/QALY), Baltimore ($18 333/QALY) and Los Angeles ($86 117/QALY). Interventions designed to improve antiretroviral therapy initiation provided greater value than other treatment engagement interventions. No single intervention was projected to reduce HIV incidence by more than 10.1% in any city. Conclusion: Combination implementation strategies should be tailored to local epidemiological contexts to provide the most value. Complementary strategies addressing factors hindering access to HIV care will be necessary to meet targets for HIV elimination in the United States. Abstract : Supplemental Digital Content is available in the text